A conceptual model of factors affecting e-commerce adoption by SME owner/managers in Jordan. (2016) - Alrousan, Mohammad Kasem; Jones, Eleri
Since the internet revolution, internet usage in business environment (e-commerce) has changed the way of doing business in SMEs. It is well known that e-commerce is essential for SMEs in enhancing their competitiveness, productivity, enlarge market and cost reduction. However, Jordan is facing slow adoption of e-commerce by SMEs. This paper reviews the strengths and weaknesses of the major models and theories relevant to technology adoption: technology acceptance model, theory of reasoned action, technology-organisation-environment, diffusion of innovation and Hofstede's cultural dimensions. Also, the literature review shows the most common sequences in level of e-commerce adoption in SMEs: Rao model; Daniel model; Rayport and Jaworski model; Lefebvrea et al. model and leadership typologies. On the bases of these theories and models, a conceptual framework for SMEs' e-commerce adoption level in Jordan is suggested. This conceptual framework can be tested empirically for SMEs in Jordan as well as other Arab countries.